Iravaiyēḷla āṣāmāṣī : Abhinandana sañcika (Ḍā. Rāvūru Abhinandana Samiti Pracuraṇa, 1979)
Volume felicitating Ravuru Venkata Satyanarayana Rao, b. 1913, Telugu writer and journalist; comprises brief articles on the life and works of the subject.